Financial Performance of PSEs Post-Disinvestment - Singh, Rakhi; Agrawal, Vijay (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
India being a developing economy has adopted the concept of mixed economy wherein both private and public sector were allowed to industrialize the country except few restricted sector. PSEs controlled by the government played an instrumental role in servicing the country in infrastructure and public services. Since there were lots of political intervention because of which the PSEs derailed from the profit making objective and turned to drainage of wealth which were once referred to be temples of modern India. The PSEs were also suddenly exposed to Global competition which they were not used for operating under protected environment. The level playing field and competition affected the financial performances of PSEs. The paper elucidates the various financial ratios over a period of 10 years and analyzed the performance of the PSEs resurrecting focusing on other factors of their sustainability.